2002
DOI: 10.1073/pnas.082110999
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic shift of VEGF isoforms with a transient and selective progesterone-induced expression of VEGF189regulates angiogenesis and vascular permeability in human uterus

Abstract: A key mechanism underlying physiological angiogenesis of the human endometrium is its ability to regenerate the vascular capillary network and to perform vascular remodeling (i.e., development of spiral arteries). Vascular endothelial growth factor (VEGF) is associated with angiogenesis and capillary permeability in this tissue. VEGF is expressed as several spliced variants, its main human isoforms contain 121 and 165 aa; 17␤-estradiol (E2) increases endometrial VEGF, possibly in all isoforms. Here we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 45 publications
7
70
1
3
Order By: Relevance
“…The production of VEGF isoforms with high molecular weight (i.e. VEGF 189 ), characterized by a lower solubility, could explain these results, as demonstrated in the endometrium when it is stimulated by a modified steroid milieu (Ancelin et al 2002). In addition, it cannot be excluded that a change in the local heparin concentration or in the composition of cell surface heparan sulphate may condition VEGF bioavailability in the follicle (Robinson & Stringer 2001).…”
Section: Follicular Vegf In Pig Vascular Remodelling · a Martelli Andmentioning
confidence: 97%
“…The production of VEGF isoforms with high molecular weight (i.e. VEGF 189 ), characterized by a lower solubility, could explain these results, as demonstrated in the endometrium when it is stimulated by a modified steroid milieu (Ancelin et al 2002). In addition, it cannot be excluded that a change in the local heparin concentration or in the composition of cell surface heparan sulphate may condition VEGF bioavailability in the follicle (Robinson & Stringer 2001).…”
Section: Follicular Vegf In Pig Vascular Remodelling · a Martelli Andmentioning
confidence: 97%
“…VEGF 188 mRNA transcription occurs as a late event during lipogenesis distinct from earlier induction of VEGF 120 and VEGF 164 mRNAs during differentiation (45). In the human uterus, 17␤-estradiol increases endometrial expression of all VEGF isoforms, whereas progesterone selectively increases the expression of the VEGF 189 isoform (46). Studies in hyperoxic acute lung injury by Corne et al (47) show that interleukin-13 selectively stimulates VEGF 164 , whereas interleukin-13 plus hyperoxia stimulate VEGF 120 and VEGF 188 .…”
Section: Tgf-␤1 Stimulates Vegf 164 Via Mkk3-p38-dependent Pathwaymentioning
confidence: 99%
“…Various studies have now shown that the different VEGFA isoforms are present in the endometrium (Charnock-Jones et al 1993, Halder et al 2000, Sharkey et al 2000, Ancelin et al 2002, Niklaus et al 2002, Sugino et al 2002. As in other tissues, VEGFA 164 is believed to be the dominant isoform in human endometrium.…”
Section: Vascular Endothelial Growth Factor-amentioning
confidence: 99%